Miguel Ángel Bonilla Obando: A revolutionary full of mysticism and love for education and his people (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
We have ventured into the study of the life and work of the hero Miguel Bonilla Obando because he is a human being with extraordinary qualities and values who must defend the revolutionary ideals and reinventions of the people. Second, becoming a teacher, example, love, conviction and passion for sharing the skills of a university that has defenders of quality and quality education, being a student leader and representative of the interests of the university community. For these qualities and for their part in the confrontation of the somatic tyranny that led them to life for the causes and that will serve as this humiliation to motivate an arduous work that translates into a great work of the values of Professor Bonilla, the revolutionary that he must be killed. Honor and glory for the death of our UNAN- Managua.
Keywords: Revolution; teacher; people; anthropology; history